A method for preparing ZnO / ZnSe / Ag nanocomposite material

By preparing ZnO/ZnSe/Ag nanocomposites and using in-situ synthesis of heterojunction and surface-loaded metal particles, the problem of low visible light utilization rate of ZnO materials is solved, significantly improving the photoelectrochemical performance of the material, and the photocurrent density reaches 257.6uA/cm2.

CN116598374BActive Publication Date: 2025-04-08NAT UNIV OF DEFENSE TECH
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202310235710.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-03-13
Publication Date
2025-04-08
Estimated Expiration
2043-03-13

AI Technical Summary

Technical Problem

The low utilization rate of ZnO materials for visible light limits its application in the field of photoelectrochemistry, especially in broadening the utilization of the solar spectrum.

Method used

By preparing ZnO/ZnSe/Ag nanocomposites, the photoelectric response performance of the material is improved by synthesising heterojunction and surface-loaded metal particles in situ. The specific steps include spin-coating the ZnO seed layer on the FTO substrate, growing the ZnO nanorod array by hydrothermal method, preparing the ZnO/ZnSe core-shell heterojunction by chemical vapor deposition method, and depositing Ag nanoparticles on its surface.

Benefits of technology

When the light intensity is 100mW/cm2 and the applied bias voltage is 0.8V, the photocurrent density of ZnO/ZnSe/Ag material is 24 times that of ZnO material, up to 257.6uA/cm2, significantly improving the photoelectrochemical performance of the material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116598374B_ABST
    Figure CN116598374B_ABST
Patent Text Reader

Abstract

The invention discloses a method for preparing a ZnO / ZnSe / Ag nanocomposite material, comprising: S1, cleaning a FTO substrate; S2, spin coating a ZnO seed layer on the FTO substrate; S3, growing a ZnO nanorod array by a hydrothermal method; S4, preparing a ZnO / ZnSe core-shell heterojunction by a chemical vapor deposition method; S5, preparing a ZnO / ZnSe / Ag nanocomposite material. The invention utilizes in-situ synthesis of heterojunctions, and metal particles are loaded on the surface. The preparation process is simple, repeatable, and low in cost. The ZnO / ZnSe / Ag nanocomposite material has a good advantage in the field of photoelectrochemistry. When the light intensity is 100mW / cm 2 When the bias voltage is 0.8V, the photocurrent density of ZnO / ZnSe / Ag material is 24 times that of pure ZnO material, reaching 257.6uA / cm 2 .
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of nano-photoelectronic materials, and more specifically, to a method for preparing a ZnO / ZnSe / Ag nano-composite material. Background Art

[0002] Since the study of the photoelectric properties of oxide semiconductor materials, they have been favored by many researchers. Not only are there many literatures that prove their unique photoelectric properties in theory, but also, in a large number of experimental studies, many conclusions have been obtained that confirm the potential application of semiconductor oxides in the field of photoelectrochemistry. Photoelectrochemistry (PEC) has always been a hot topic in the fields of photoelectric detection, photoelectric sensing, and semiconductor biosensing. ZnO, as a wide bandgap oxide semiconductor material (Eg = 3.37 eV) commonly used in ultraviolet detection devices, has a good response to ultraviolet light, but ultraviolet light only accounts for about 5% of the solar spectrum, which makes the utilization rate of ZnO materials for light extremely low, limiting its utilization of the visible light region, while heterojunctions can broaden its utilization of the solar spectrum. Since the PN junction has a built-in electric field, it can achieve effective separation of electrons and holes, so the PN junction is often used in the study of PEC. Zinc selenide (ZnSe) is an important II-VI group direct bandgap semiconductor with a bandgap width of 2.7 eV. It has important applications in photoelectric detection, photovoltaic devices, and light-emitting devices. In addition to semiconductor coupling into heterojunctions, methods such as noble metal surface deposition, surface sensitization, quantum dot modification, and metal ion doping can also broaden the photoelectric response performance of materials. The localized surface plasmon resonance of noble metal nanoparticles has attracted attention in many aspects and can greatly improve the ability to capture light. This characteristic is very important for improving the performance of nanostructured optoelectronic devices, giving nanoparticles a greater advantage in light capture and absorption. Summary of the invention

[0003] The purpose of the present invention is to provide a method for preparing a ZnO / ZnSe / Ag nanocomposite material to overcome the defects of the prior art.

[0004] In order to achieve the above object, the technical solution adopted by the present invention is as follows:

[0005] A method for preparing a ZnO / ZnSe / Ag nanocomposite material comprises the following steps:

[0006] S1, cleaning the FTO substrate;

[0007] S2, spin coating a ZnO seed layer on the FTO substrate;

[0008] S3, growing ZnO nanorod arrays by hydrothermal method;

[0009] S4, preparing ZnO / ZnSe core-shell heterojunction by chemical vapor deposition;

[0010] S5. Prepare ZnO / ZnSe / Ag nanocomposite materials.

[0011] Furthermore, the step S1 specifically includes: firstly ultrasonically cleaning the FTO substrate with acetone, anhydrous ethanol and deionized water in sequence, then drying it in a fume hood, and then cleaning the dried FTO conductive glass with a plasma machine and taking it out for standby use.

[0012] Furthermore, the step S2 is specifically as follows: preparing a 4-6 mmol / L zinc acetate solution, taking the zinc acetate solution with a rubber-tipped dropper and dropping it on the cleaned FTO substrate, spin coating at a low speed of 500r for 10s and a high speed of 3000r for 15s, drying on a 60°C heating plate, repeating 2-3 times to obtain a ZnO seed crystal layer, and then calcining the above product at a high temperature of 300°C for 20min.

[0013] Furthermore, the step S3 is specifically as follows: 0.04-0.06 mmol / L zinc nitrate hexahydrate solution and hexamethylenetetramine solution are prepared as precursor solutions, FTO conductive glass with a ZnO seed layer attached is placed in the precursor solution to react for 3-4 hours, the FTO is taken out and slowly rinsed with deionized water, and the growth process is repeated 2-3 times after drying to obtain a ZnO nanorod array, and the ZnO nanorods are annealed at 300° C. under inert gas argon for 30 minutes, and cooled for standby use.

[0014] Furthermore, the step S4 is specifically as follows: placing the ZnO nanorods in a quartz boat and placing it at one end of the quartz tube of the chemical vapor deposition reaction furnace, placing the quartz boat containing Se powder at the other end of the quartz tube, and after sealing the quartz tube, introducing argon with a gas flow rate of about 500sccm, cleaning the pipeline for 10 minutes, ensuring that the argon passes through the Se powder first and then passes through the ZnO nanorods, the temperature of the area where the quartz boat containing the ZnO nanorods is located is set to 400°C, the temperature of the area where the quartz boat containing the Se powder is located is set to 270°C, the selenization time is set to 10 minutes, and after cleaning the pipeline, introducing argon and hydrogen in a ratio of 95:5, waiting for the temperature to rise for reaction, and taking out after cooling to obtain the product ZnO / ZnSe core-shell heterojunction.

[0015] Furthermore, the step S5 is specifically as follows: centrifuging the silver nanoparticle solution at 10,000 rpm for 5 min, taking the lower layer of solution with a pipette and dropping it on the ZnO / ZnSe core-shell heterojunction, applying external force to disperse the Ag ions on the ZnO / ZnSe core-shell heterojunction, and finally preparing a ZnO / ZnSe / Ag nanocomposite material.

[0016] Furthermore, after step S5, the following steps are further included:

[0017] S6. Photoelectrochemical performance test of ZnO / ZnSe / Ag nanocomposite materials.

[0018] Furthermore, the step S6 is specifically as follows: using the prepared ZnO / ZnSe / Ag nanocomposite material as the working electrode of the three-electrode system of the electrochemical workstation, using an LED white light source with a wavelength range of 430 to 720 nm as the light source, using the Ag / AgCl electrode as the reference electrode, and the platinum electrode as the counter electrode, testing the photocurrent, dark current, and transient response of the ZnO / ZnSe / Ag material, and finally comparing the photoelectric properties of the electrodes.

[0019] Furthermore, the length of the ZnO nanorods is 6.4 um.

[0020] Furthermore, the maximum value of the photocurrent density is 673.7uA / cm 2 , the response time is 1.803ms.

[0021] Compared with the prior art, the advantages of the present invention are as follows: the preparation method of the ZnO / ZnSe / Ag nanocomposite material provided by the present invention utilizes in-situ synthesis of heterojunction and surface loading of metal particles, the preparation process is simple, the repeatability is high, the cost is low, and the ZnO / ZnSe / Ag nanocomposite material has a good advantage in the field of photoelectrochemistry. 2 When the bias voltage is 0.8V, the photocurrent density of ZnO / ZnSe / Ag material is 24 times that of pure ZnO material, reaching 257.6uA / cm 2 . BRIEF DESCRIPTION OF THE DRAWINGS

[0022] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0023] Figure 1 (a) is a schematic diagram of the sample preparation process of Example 3 of the present invention; Figure 1 (b) is a transmission electron microscope image (TEM) of the sample of Example 2 of the present invention; Figure 1 (c) is a scanning electron microscope image (SEM) of the sample of Example 3 of the present invention.

[0024] Figure 2 This is the X-ray diffraction spectrum (XRD) of the sample of Example 2 of the present invention.

[0025] Figure 3 It is the Raman spectra of samples of Examples 1 and 2 of the present invention.

[0026] Figure 4 3 is a photocurrent diagram of samples of Examples 1, 2 and 3 of the present invention at a bias voltage of -0.8V to 0.6V.

[0027] Figure 5 (a) is a graph showing the photoelectric response of the sample of Example 3 of the present invention at different bias voltages; Figure 5 (b) is the results of the samples of Examples 1, 2 and 3 of the present invention at a bias voltage of 0.8 V and a light intensity of 100 mW / cm 2 Photoelectric response curve below. DETAILED DESCRIPTION

[0028] The preferred embodiments of the present invention are described in detail below in conjunction with the accompanying drawings so that the advantages and features of the present invention can be more easily understood by those skilled in the art, thereby making a clearer and more definite definition of the protection scope of the present invention.

[0029] Embodiment 1

[0030] In this embodiment, the ZnO nanorod arrays were prepared according to the following steps:

[0031] a) Treat the FTO substrate. Ultrasonic clean the FTO substrate with acetone, anhydrous ethanol and deionized water in sequence, for about 10 minutes each time, and dry it in a fume hood. After drying, clean the FTO conductive glass with a plasma machine for about 40 seconds and take it out for use.

[0032] b) Spin-coat the ZnO seed layer on the FTO. Prepare 4-6 mmol / L zinc acetate solution, use a rubber-tipped dropper to take an appropriate amount of zinc acetate solution and drop it on the cleaned FTO substrate, spin-coat at a low speed of 500r for 10s and a high speed of 3000r for 15s, dry on a 60°C hot plate, repeat 2-3 times to obtain a ZnO seed layer, and then calcine the above product at a high temperature of 300°C for about 20 minutes.

[0033] c) Grow ZnO nanorod arrays by hydrothermal method. Prepare 0.04-0.06mmol / L zinc nitrate hexahydrate solution and hexamethylenetetramine solution as precursor solution, place FTO conductive glass with ZnO seed layer attached in the precursor solution to react for 3-4 hours, then take out FTO and slowly rinse with deionized water, dry and repeat the growth process 2-3 times to obtain ZnO nanorod array, finally anneal the ZnO nanorods at 300℃ under inert gas argon for 30 minutes, cool and set aside.

[0034] d) Photoelectrochemical performance test of ZnO nanorod array. The prepared ZnO nanorod array was used as the working electrode of the three-electrode system of the electrochemical workstation, the light source used was an LED white light source with a wavelength range of 430-720nm, the Ag / AgCl electrode was used as the reference electrode, and the platinum electrode was used as the counter electrode. The photocurrent, dark current, and transient response of the ZnO nanorods were tested, and finally the photoelectric performance of the electrodes was compared.

[0035] Embodiment 2

[0036] In this embodiment, the ZnO / ZnSe core-shell heterojunction is prepared according to the following steps:

[0037] a) Treat the FTO substrate. Ultrasonic clean the FTO substrate with acetone, anhydrous ethanol and deionized water in sequence, for about 10 minutes each time, and dry it in a fume hood. After drying, clean the FTO conductive glass with a plasma machine for about 40 seconds and take it out for use.

[0038] b) Spin-coat the ZnO seed layer on the FTO. Prepare 4-6 mmol / L zinc acetate solution, use a rubber-tipped dropper to take an appropriate amount of zinc acetate solution and drop it on the cleaned FTO substrate, spin-coat at a low speed of 500r for 10s and a high speed of 3000r for 15s, dry on a 60°C hot plate, repeat 2-3 times to obtain a ZnO seed layer, and then calcine the above product at a high temperature of 300°C for about 20 minutes.

[0039] c) Grow ZnO nanorod arrays by hydrothermal method. Prepare 0.04-0.06mmol / L zinc nitrate hexahydrate solution and hexamethylenetetramine solution as precursor solution, place FTO conductive glass with ZnO seed layer attached in the precursor solution to react for 3-4 hours, then take out FTO and slowly rinse with deionized water, dry and repeat the growth process 2-3 times to obtain ZnO nanorod array, finally anneal the ZnO nanorods at 300℃ under inert gas argon for 30 minutes, cool and set aside.

[0040] d) Prepare ZnO / ZnSe core-shell heterojunction by chemical vapor deposition. Place ZnO nanorods in a quartz boat and place it at one end of the quartz tube of a chemical vapor deposition reactor. Place the quartz boat containing Se powder at the other end of the quartz tube. After sealing the quartz tube, introduce argon gas with a gas flow rate of about 500 sccm, clean the pipeline for about 10 minutes, ensure that the argon gas passes through the Se powder first, and then passes through the ZnO nanorods. The temperature of the area where the quartz boat containing ZnO nanorods is located is set to 400°C, and the temperature of the area where the quartz boat containing Se powder is located is set to 270°C. The selenization time is set to 10 minutes. After cleaning the pipeline, introduce argon and hydrogen in a ratio of 95:5, wait for the temperature to rise for reaction, and take it out after cooling to obtain the product ZnO / ZnSe core-shell heterojunction.

[0041] e) Photoelectrochemical performance test of ZnO / ZnSe core-shell heterojunction. The prepared ZnO / ZnSe / core-shell heterojunction was used as the working electrode of the three-electrode system of the electrochemical workstation, the light source used was an LED white light source with a wavelength range of 430-720nm, the Ag / AgCl electrode was used as the reference electrode, and the platinum electrode was used as the counter electrode. The photocurrent, dark current, and transient response of the ZnO / ZnSe core-shell heterojunction were tested, and the photoelectric performance of the electrodes was finally compared.

[0042] Embodiment 3

[0043] In this embodiment, the ZnO / ZnSe / Ag nanocomposite material is prepared according to the following steps:

[0044] a) Treat the FTO substrate. Ultrasonic clean the FTO substrate with acetone, anhydrous ethanol and deionized water in sequence, for about 10 minutes each time, and dry it in a fume hood. After drying, clean the FTO conductive glass with a plasma machine for about 40 seconds and take it out for use.

[0045] b) Spin-coat the ZnO seed layer on the FTO. Prepare 4-6 mmol / L zinc acetate solution, use a rubber-tipped dropper to take an appropriate amount of zinc acetate solution and drop it on the cleaned FTO substrate, spin-coat at a low speed of 500r for 10s and a high speed of 3000r for 15s, dry on a 60°C hot plate, repeat 2-3 times to obtain a ZnO seed layer, and then calcine the above product at a high temperature of 300°C for about 20 minutes.

[0046] c) Grow ZnO nanorod arrays by hydrothermal method. Prepare 0.04-0.06mmol / L zinc nitrate hexahydrate solution and hexamethylenetetramine solution as precursor solution, place FTO conductive glass with ZnO seed layer attached in the precursor solution to react for 3-4 hours, then take out FTO and slowly rinse with deionized water, dry and repeat the growth process 2-3 times to obtain ZnO nanorod array, finally anneal the ZnO nanorods at 300℃ under inert gas argon for 30 minutes, cool and set aside.

[0047] d) Prepare ZnO / ZnSe core-shell heterojunction by chemical vapor deposition. Place ZnO nanorods in a quartz boat and place it at one end of the quartz tube of a chemical vapor deposition reactor. Place the quartz boat containing Se powder at the other end of the quartz tube. After sealing the quartz tube, introduce argon gas with a gas flow rate of about 500 sccm, clean the pipeline for about 10 minutes, ensure that the argon gas passes through the Se powder first, and then passes through the ZnO nanorods. The temperature of the area where the quartz boat containing ZnO nanorods is located is set to 400°C, and the temperature of the area where the quartz boat containing Se powder is located is set to 270°C. The selenization time is set to 10 minutes. After cleaning the pipeline, introduce argon and hydrogen in a ratio of 95:5, wait for the temperature to rise for reaction, and take it out after cooling to obtain the product ZnO / ZnSe core-shell heterojunction.

[0048] e) Preparation of ZnO / ZnSe / Ag nanocomposite materials. The silver nanoparticle solution was centrifuged at 10,000 rpm for 5 min, the lower layer solution was taken, and a proper amount of the lower layer solution was dropped on the ZnO / ZnSe core-shell heterojunction using a pipette, and a certain external force was applied to disperse the Ag ions on the ZnO / ZnSe core-shell heterojunction, and finally a ZnO / ZnSe / Ag nanocomposite material was prepared, and it was naturally dried and set aside.

[0049] f) Photoelectrochemical performance test of ZnO / ZnSe / Ag nanocomposite materials. The prepared ZnO / ZnSe / Ag nanocomposite materials were used as the working electrode of the three-electrode system of the electrochemical workstation, the light source used was an LED white light source with a wavelength range of 430-720nm, the Ag / AgCl electrode was used as the reference electrode, and the platinum electrode was used as the counter electrode. The photocurrent, dark current, and transient response of the ZnO / ZnSe / Ag material were tested, and finally the photoelectric performance of the electrodes was compared.

[0050] By comparing the first, second and third embodiments, it can be seen that there is a hierarchical relationship among the three. The third embodiment is carried out on the basis of the second embodiment, and the second embodiment is completed on the basis of the first embodiment.

[0051] For all embodiments in this specific implementation mode, refer to Figure 1 (a) is a flow chart of the preparation process. First, a ZnO seed layer is prepared on FTO. The ZnO is vertically oriented along the c-axis to form a ZnO nanorod array by a hydrothermal method. Then, Se vapor is deposited on the surface of the ZnO nanorods along the gas flow direction under a mixture of N2 and H2 by chemical vapor deposition. The ZnSe shell layer is sintered on the surface of the ZnO nanorods to form a ZnO / ZnSe nanocomposite material. Finally, Ag nanoparticles are dripped on the surface with a pipette gun and dried to form a ZnO / ZnSe / Ag nanocomposite material. Figure 1 (b) shows a transmission electron micrograph of a ZnO nanorod, from which it can be clearly seen that a thin layer of ZnSe is formed on the outer layer of the ZnO nanorod, indicating that a ZnO / ZnSe core-shell structure is formed. Figure 1 (c) Scanning electron microscopy image showing Ag nanoparticles attached to the ZnO / ZnSe core-shell heterojunction.

[0052] Figure 2This is the X-ray diffraction pattern of the sample obtained in Example 2. As can be seen from the figure, the diffraction peaks corresponding to the (002), (101), (102) and (103) crystal planes are fully tested, and by comparing with the standard PDF card, they correspond to the wurtzite structure of ZnO. The peak intensity is the largest at the (002) crystal plane, which indicates that the ZnO nanorods grow preferentially along the c-axis orientation on the FTO surface, and their crystallization quality is good. The small peak at 27.1° corresponds to the (111) crystal plane of ZnSe, and only one weak peak appears, indicating that in the ZnO / ZnSe core-shell heterojunction material, the content of ZnSe is lower than that of ZnO.

[0053] Figure 3 Figures (a) and (b) are the Raman spectra of ZnO nanorods and ZnO / ZnSe core-shell heterojunction grown on FTO conductive glass, respectively. It can be clearly seen from the two curves in the figure that the two Raman spectra at 205 and 250 cm -1 The peaks at 332 cm correspond to the transverse optical (TO) phonon mode and the longitudinal optical (LO) phonon mode of the cubic sphalerite ZnSe crystal structure. -1 The peak at 440 cm-1 corresponds to the ZnO multiphoton (MP) scattering process. -1 The peak at belongs to the high-frequency branch of the non-polar optical phonon mode of ZnO, which is one of the characteristic modes of wurtzite ZnO. The strong E2 mode indicates that the ZnO nanorods grow well along the c-axis. This is consistent with the previous XRD and TEM results. These Raman experiments confirm that we have successfully replaced O with Se on the surface of ZnO nanorods and synthesized the ZnO / ZnSe core-shell heterojunction in situ with good crystal quality.

[0054] Figure 4 The photocurrent graph of samples of Examples 1, 2 and 3 of the present invention at a bias voltage of -0.8V to 0.6V is shown in the figure. As can be seen from the figure, under visible light irradiation, when a bias voltage within a certain range is applied, the photocurrent density of the ZnO / ZnSe core-shell heterojunction material increases compared to the pure ZnO nanorod material. The photocurrent density of the ZnO / ZnSe / Ag nanocomposite material is greater than that of the ZnO / ZnSe core-shell heterojunction material, and can reach up to 673.7uA / cm 2 This is because ZnO and ZnSe form a heterojunction, and their interface constitutes a space charge region, forming a built-in electric field, which can promote the effective separation of photogenerated electron-hole pairs. In addition, Ag nanoparticles with a diameter of 60nm attached to the surface of the ZnO / ZnSe core-shell heterojunction can promote the absorption of photons in the material, thereby increasing its photocurrent density.

[0055] Figure 5(a) is a photoelectrochemical performance diagram of the sample of Example 3 of the present invention. Under visible light irradiation, during the dark / light alternating cycle, the photocurrent density of the ZnO / ZnSe / Ag nanocomposite material increases with the increase of the bias voltage and decreases with the increase of time. As time goes by, the ZnO / ZnSe / Ag nanocomposite material will produce photocorrosion when performing photoelectrochemical testing, which will cause certain damage to the material structure, so that when the light is irradiated again, the material cannot produce more photogenerated carriers under visible light than the last time. Moreover, in the preparation process of the ZnO / ZnSe / Ag nanocomposite material, it has a small amount of interface defects, and the interface defects can cause the recombination of electron-hole pairs. As a result, the photocurrent density will decrease with time, but will eventually tend to a stable value, and the separation and recombination of the photogenerated electron-hole pairs will reach an equilibrium state.

[0056] Figure 5 (b) is the photoelectrochemical performance diagram of samples of Examples 1, 2 and 3 of the present invention. It can be seen from the figure that when the bias voltage is 0.8V and the light intensity is 100mW / cm 2 Under the condition of high photocurrent density, the photocurrent density of ZnO / ZnSe / Ag nanocomposite is about 24 times that of pure ZnO nanorod material, and its photocurrent density is as high as 257.6uA / cm 2 This shows that the synthesis of heterojunction and the modification of Ag nanoparticles can indeed promote the separation of photogenerated electron-hole pairs in the material and enhance the photoelectric response intensity of the material.

[0057] Although the embodiments of the present invention are described in conjunction with the accompanying drawings, the patent owner may make various variations or modifications within the scope of the appended claims. As long as they do not exceed the protection scope described in the claims of the present invention, they should be within the protection scope of the present invention.

Claims

1. A method for preparing a ZnO / ZnSe / Ag nanocomposite material, characterized in that: The following steps are involved: S1, cleaning the FTO substrate; S2, spin coating a ZnO seed layer on the FTO substrate; S3, growing ZnO nanorod arrays by hydrothermal method; S4, preparing ZnO / ZnSe core-shell heterojunction by chemical vapor deposition; S5. preparing ZnO / ZnSe / Ag nanocomposite materials; The step S2 is specifically as follows: preparing a 4-6 mmol / L zinc acetate solution, using a rubber-tipped dropper to drop the zinc acetate solution onto a cleaned FTO substrate, spin coating at a low speed of 500 r for 10 s and a high speed of 3000 r for 15 s, drying on a 60° C. heating plate, repeating 2-3 times to obtain a ZnO seed crystal layer, and then calcining the above product at a high temperature of 300° C. for 20 min.

2. The method for preparing the ZnO / ZnSe / Ag nanocomposite material according to claim 1, characterized in that: The step S1 specifically includes: firstly ultrasonically cleaning the FTO substrate with acetone, anhydrous ethanol and deionized water in sequence, then drying it in a fume hood, and then cleaning the dried FTO conductive glass with a plasma machine and taking it out for standby use.

3. The method for preparing the ZnO / ZnSe / Ag nanocomposite material according to claim 1, characterized in that: The step S3 is specifically as follows: preparing 0.04-0.06 mmol / L zinc nitrate hexahydrate solution and hexamethylenetetramine solution as precursor solutions, placing FTO conductive glass with a ZnO seed crystal layer attached in the precursor solution to react for 3-4 hours, taking out the FTO and slowly rinsing it with deionized water, and then repeating the growth process 2-3 times after drying to obtain a ZnO nanorod array, and then annealing the ZnO nanorods at 300° C. under inert gas argon for 30 minutes, and cooling for standby use.

4. The method for preparing the ZnO / ZnSe / Ag nanocomposite material according to claim 1, characterized in that: The step S4 is specifically as follows: placing the ZnO nanorods in a quartz boat and placing it at one end of the quartz tube of the chemical vapor deposition reaction furnace, placing the quartz boat containing Se powder at the other end of the quartz tube, and after sealing the quartz tube, introducing argon gas with a gas flow rate of 500sccm, cleaning the pipeline for 10 minutes, ensuring that the argon gas passes through the Se powder first and then passes through the ZnO nanorods, the temperature of the area where the quartz boat containing the ZnO nanorods is located is set to 400°C, the temperature of the area where the quartz boat containing the Se powder is located is set to 270°C, the selenization time is set to 10 minutes, and after cleaning the pipeline, introducing argon gas and hydrogen gas in a ratio of 95:5, waiting for the temperature to rise for reaction, and taking out after cooling to obtain the product ZnO / ZnSe core-shell heterojunction.

5. The method for preparing the ZnO / ZnSe / Ag nanocomposite material according to claim 1, characterized in that: The step S5 is specifically as follows: centrifuging the silver nanoparticle solution at 10,000 rpm for 5 minutes, taking the lower layer of solution with a pipette and dropping it on the ZnO / ZnSe core-shell heterojunction, applying external force to disperse the Ag ions on the ZnO / ZnSe core-shell heterojunction, and finally preparing a ZnO / ZnSe / Ag nanocomposite material.

6. The method for preparing the ZnO / ZnSe / Ag nanocomposite material according to claim 1, characterized in that: The step S5 further includes: S6. Photoelectrochemical performance test of ZnO / ZnSe / Ag nanocomposite materials.

7. The method for preparing the ZnO / ZnSe / Ag nanocomposite material according to claim 6, characterized in that: The step S6 specifically comprises: using the prepared final product ZnO / ZnSe / Ag nanocomposite material as the working electrode of the three-electrode system of the electrochemical workstation, using an LED white light source with a wavelength range of 430 to 720 nm as the light source, using an Ag / AgCl electrode as a reference electrode, and a platinum electrode as a counter electrode, testing the photocurrent, dark current, and transient response of the ZnO / ZnSe / Ag material, and performing photoelectrochemical tests on the ZnO nanorods and the ZnO / ZnSe core-shell heterojunction under the same conditions, and finally comparing the photoelectric properties of the electrodes.

8. The method for preparing the ZnO / ZnSe / Ag nanocomposite material according to claim 3, characterized in that: The length of the ZnO nanorods is 6.4 um.

9. The method for preparing the ZnO / ZnSe / Ag nanocomposite material according to claim 7, characterized in that: The maximum value of the photocurrent density is 673.7uA / cm 2 , the response time is 1.803ms.

Citation Information

Patent Citations

  • Preparation method of nanometer rodlike structure light positive electrode used for quantum dot sensitization solar battery

    CN107946077A